Effect of fill properties on load−settlement behaviour of granular columns in marine clays. Issue 3 (28th June 2019) - Phanikumar, B. R.; Dayakar Babu, R.; Narasimha Rao, S.
Abstract : This paper describes an experimental investigation carried out to study the load−settlement behaviour and bulge characteristics of granular columns in a soft marine clay bed. The effects of gradation and compacted density of the granular fill material on the load response, bulge length and bulge diameter of granular columns are presented. Granular columns were formed using five kinds of crushed stone aggregates of different gradation, compacted in loose and dense states. The ultimate capacity of the composite ground, bulge diameter and bulge length were more in the case of the densely compacted granular columns than for the loosely compacted granular columns. The relative density and the angle of internal friction of the granular fills, in both loose and dense states, increased with decreasing particle size of the aggregates. Consequently, the load-carrying capacity also increased with decreasing particle size of the aggregates. The percentage increase in the ultimate capacity ranged from 106 to 210% when different aggregates were compacted in their loose and dense states. For a given gradation, the ultimate capacity increased up to an l / d ratio of 11 and decreased thereafter.